2012
DOI: 10.1002/jbmr.1594
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of β-adrenergic receptor 1, 2, or both leads to different bone phenotypes and response to mechanical stimulation

Abstract: As they age, mice deficient for the b2-adrenergic receptor (Adrb2 À/À ) maintain greater trabecular bone microarchitecture, as a result of lower bone resorption and increased bone formation. The role of b1-adrenergic receptor signaling and its interaction with b2-adrenergic receptor on bone mass regulation, however, remains poorly understood. We first investigated the skeletal response to mechanical stimulation in mice deficient for b1-adrenergic receptors and/or b2-adrenergic receptors. Upon axial compression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
83
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 49 publications
8
83
0
3
Order By: Relevance
“…In Adrb1 À /À 2 À /À 3 À /À mice, bone volume was increased in cancellous bone of vertebrae and femurs and in cortical bone of femurs at 6 weeks of age and only in cortical bone of femurs at 16 weeks of age due to the reduced bone resorption (Bouxsein et al, 2009). Tibiae from Adrb2 À /À mice but not Adrb1 À /À mice and Adrb1 À /À 2 À /À mice responded to axial compression loading similarly to those from wild-type mice (Pierroz et al, 2012). Furthermore, treatment with isoproterenol reduced cancellous and cortical bone in wild-type mice, but not in Adrb1 À /À 2 À /À mice (Pierroz et al, 2012).…”
Section: Animal Models For the Analysis Of Bone Regulation By Sympathsupporting
confidence: 53%
See 2 more Smart Citations
“…In Adrb1 À /À 2 À /À 3 À /À mice, bone volume was increased in cancellous bone of vertebrae and femurs and in cortical bone of femurs at 6 weeks of age and only in cortical bone of femurs at 16 weeks of age due to the reduced bone resorption (Bouxsein et al, 2009). Tibiae from Adrb2 À /À mice but not Adrb1 À /À mice and Adrb1 À /À 2 À /À mice responded to axial compression loading similarly to those from wild-type mice (Pierroz et al, 2012). Furthermore, treatment with isoproterenol reduced cancellous and cortical bone in wild-type mice, but not in Adrb1 À /À 2 À /À mice (Pierroz et al, 2012).…”
Section: Animal Models For the Analysis Of Bone Regulation By Sympathsupporting
confidence: 53%
“…Tibiae from Adrb2 À /À mice but not Adrb1 À /À mice and Adrb1 À /À 2 À /À mice responded to axial compression loading similarly to those from wild-type mice (Pierroz et al, 2012). Furthermore, treatment with isoproterenol reduced cancellous and cortical bone in wild-type mice, but not in Adrb1 À /À 2 À /À mice (Pierroz et al, 2012). Moreover, bone loss by ovariectomy similarly occurred in wildtype and Adrb1 À /À 2 À /À 3 À /À mice (Bouxsein et al, 2009).…”
Section: Animal Models For the Analysis Of Bone Regulation By Sympathmentioning
confidence: 53%
See 1 more Smart Citation
“…Ϫ/Ϫ mice were reminiscent of what had been previously observed upon pharmacological activation of ␤2AR signaling in mice or rats receiving daily ␤AR agonist injections (1,11,21). These observations suggested that lack of NET leads to overt stimulation of the ␤2AR expressed in osteoblasts, leading to bone loss.…”
Section: Net ϫ/ϫ Mice Have Reduced Sympathetic Outflow But High Circumentioning
confidence: 59%
“…Functional b2-adrenergic receptors were identified on murine and human osteoblasts 3 and the administration of a b2-blocker to WT mice resulted in increased cancellous bone mass. 27,47 No change in cancellous bone mass was found when b2-adrenergic receptor-deficient mice were given an intracerebroventricular (i.c.v.) infusion of leptin.…”
Section: Adipokines: Leptinmentioning
confidence: 98%